2015
DOI: 10.1177/0960327115606529
|View full text |Cite
|
Sign up to set email alerts
|

The chemical, genetic and immunological basis of idiosyncratic drug–induced liver injury

Abstract: Idiosyncratic drug reactions can be extremely severe and are not accounted for by the regular pharmacology of a drug. Thus, the mechanism of idiosyncratic drug–induced liver injury (iDILI), a phenomenon that occurs with many drugs including β-lactams, anti-tuberculosis drugs and non-steroidal anti-inflammatories, has been difficult to determine and remains a pressing issue for patients and drug companies. Evidence has shown that iDILI is multifactorial and multifaceted, which suggests that multiple ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
23
1
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(25 citation statements)
references
References 86 publications
0
23
1
1
Order By: Relevance
“…The results of the present study may provide support for the suggestion that patients with the AA genotype should use as little as possible or no hepatoprotectants during anti‐TB treatment. The present study failed to find any significant association among moderate and severe hepatotoxicity cases, which also indicated that DILI is multifactorial and multifaceted, and also that multiple cellular mechanisms may be involved . Some previous unrecognized mechanisms, including INH‐induced activation of the adaptive and innate immune system, disruption of endogenous metabolism, and mitochondrial dysfunction, may be implicated in INH hepatotoxicity .…”
Section: Discussioncontrasting
confidence: 73%
See 1 more Smart Citation
“…The results of the present study may provide support for the suggestion that patients with the AA genotype should use as little as possible or no hepatoprotectants during anti‐TB treatment. The present study failed to find any significant association among moderate and severe hepatotoxicity cases, which also indicated that DILI is multifactorial and multifaceted, and also that multiple cellular mechanisms may be involved . Some previous unrecognized mechanisms, including INH‐induced activation of the adaptive and innate immune system, disruption of endogenous metabolism, and mitochondrial dysfunction, may be implicated in INH hepatotoxicity .…”
Section: Discussioncontrasting
confidence: 73%
“…The present study failed to find any significant association among moderate and severe hepatotoxicity cases, which also indicated that DILI is multifactorial and multifaceted, and also that multiple cellular mechanisms may be involved. 37 Some previous unrecognized mechanisms, including INH-induced activation of the adaptive and innate immune system, disruption of endogenous metabolism, and mitochondrial dysfunction, may be implicated in INH hepatotoxicity. 38 Idiosyncratic DILI reactions are mediated by the adaptive immune response, and the development and severity of injury is determined by the conflict between the hazardous stress and adaptive responses within the hepatocytes and the innate and adaptive immune systems.…”
Section: Discussionmentioning
confidence: 99%
“…Several mechanisms have been proposed to contribute to drug-induced liver injury, and it is likely that multiple concerted pathways are involved [44,45,46]. Formation of reactive metabolites is hypothesized to be a key initiating event in tyrosine kinase inhibitor-induced hepatotoxicity.…”
Section: Downstream Toxicity Mechanisms Of Tyrosine Kinase Inhibitorsmentioning
confidence: 99%
“…Furthermore, a genome-wide association study (GWAS) identified the HLA B*57:01 allele as a strong risk factor for flucloxacillin-induced DILI, with an odds ratio of 80.6, indicative for an important role of the immune system in the mechanism of liver toxicity (Daly et al, 2009). Many forms of idiosyncratic DILI are believed to have an immunological basis, in which covalent binding of drugs and/or metabolites to proteins may play an important role by generation of a hapten and by causing cellular stress, leading to the release of so-called danger signals which can stimulate the immune response (Uetrecht, 2007;Tailor et al, 2015). Like many other penicillin-like antibiotics, the reactive β-lactam-rings of flucloxacillin and its active metabolite 5 0 -hydroxymethyl-flucloxacillin (5 0 -HM-FLX, Figure 1) have been shown to react with lysine-residues of proteins thereby forming potential haptens (Jenkins et al, 2009).…”
Section: Introductionmentioning
confidence: 99%